Creating Special Effect With Adobe Photoshop 7.0 A step by step approach - Palani,Murugappan (Kuala Lumpur Venton Publishing, 2003)
This book is written using a step-by-step approach for all users wanting to learn some of the spesial effects that can be created using some of the basic and advanced functions that Photoshop offres. Some of the special effects covered include creatin
Include index
Keywords: Adobe Photoshop; Computer graphics